2008
DOI: 10.1007/s10493-008-9189-z
|View full text |Cite
|
Sign up to set email alerts
|

Development, long-term survival, and the maintenance of fertility in Neoseiulus californicus (Acari: Phytoseiidae) reared on an artificial diet

Abstract: The effectiveness of non-prey food items, such as pollen, honeydew, and microbes, in maintaining phytoseiid mite populations is widely accepted. However, the availability of such naturally occurring non-prey foods varies with the season and surrounding environment; thus, it is difficult to manipulate and maintain supplies of these food sources. A great deal of research has examined the development and reproduction of phytoseiid mites on artificial diets. Although phytoseiid mites frequently develop, several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…The artificial diet was composed of honey (Meli N.V., Veurne, Belgium), sucrose (MP Biomedicals LLC, Illkirch, France), tryptone (Fluka Analytical, SigmaAldrich Co., St. Louis, USA), yeast extract (Duchefa, Haarlem, The Netherlands), fresh hen's egg yolk, and distilled water, and was prepared according to Ogawa and Osakabe (2008), with some modifications as explained below. Two diets were prepared.…”
Section: Preparation Of Artificial Dietmentioning
confidence: 99%
See 3 more Smart Citations
“…The artificial diet was composed of honey (Meli N.V., Veurne, Belgium), sucrose (MP Biomedicals LLC, Illkirch, France), tryptone (Fluka Analytical, SigmaAldrich Co., St. Louis, USA), yeast extract (Duchefa, Haarlem, The Netherlands), fresh hen's egg yolk, and distilled water, and was prepared according to Ogawa and Osakabe (2008), with some modifications as explained below. Two diets were prepared.…”
Section: Preparation Of Artificial Dietmentioning
confidence: 99%
“…To examine the development and reproduction of individual A. swirskii, modified Munger cells were used as rearing microcosms (Ogawa and Osakabe 2008). Each cell consisted of a transparent acrylic board (top board; 40 9 40 mm, 2 mm thick) with a 19 mm diameter hole in the center, a black acrylic board (middle board; 40 9 40 mm, 5 mm thick) with a 18 mm diameter hole in the center, and another black acrylic board (bottom board; 40 9 40 mm, 2 mm thick) with a 1 mm diameter hole in the center.…”
Section: Rearing Microcosmsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that the effect of sucrose on the survival of S. takahashii may be greater than on S. japonicus and O. kashmirica benefica; however, it is not clear that females fed sucrose died due to their physiological longevity even in S. takahashii. Ogawa and Osakabe (2008) suggested that adult female Neoseiulus californicus (McGregor) (Acari: Phytoseiidae) reared on artificial diets laid few eggs, but could survive longer than ovipositing females reared on T. urticae. In this study, females fed sucrose did not oviposit in all three species.…”
Section: Discussionmentioning
confidence: 99%